Numerical Modeling and Clinical Evaluation of Pulsed Dye Laser and Copper Vapor Laser in Skin Vascular Lesions Treatment - Klyuchareva, Svetlana Viktorovna; Ponomarev, Igor Vladimirovich; Pushkareva, Alexandra Evgenyevna (Journal of Lasers in Medical Sciences, 2018)
Introduction: Different yellow lasers have been successfully used for the treatment of vascular lesions. This study is aimed to ascertain the role and efficiency of copper vapor lasers (CVLs) and pulsed dye lasers (PDLs) for the treatment of vascular lesions using numerical modeling and to compare results with our clinical experience. In this study we aimed to develop criteria for the choice of more efficient laser exposure mode, investigate more relevant modes of laser irradiation to ensure selective photothermolysis of target vessels, and compare the CVL and PDL efficiency in the course of patients with skin vascular lesions (SVL) treatment. Methods: We performed numerical simulation of the processes of heating a vessel with CVL and PDL to temperatures at which its coagulation could occur. Calculated fluencies were compared with clinical results of laser therapy performed on 1242 patients with skin hemangiomas and vascular malformations (SHVM), including 635 patients treated with CVL and 607 patients treated with PDL. PDL and CVL provided excellent results in 40 and ten days after treatment. The treatment was not painful. Patients did not need anesthesia. Postoperative crusts were greater with PDL than with CVL. Results: Results of computer simulation of a selective vessel heating using PDL and CVL radiation are presented. By results obtained, depth of the location and sizes of vessels that could be selectively heated to more than 75°C are determined. Conclusion: Based on calculated and clinical data, the heating mode for dysplastic vessels using a series of CVL micropulses could be regarded to be safer and more efficient than the mode of a PDL short, powerful pulse.